Comparative phylogeography of two free‐living cosmopolitan cyanobacteria: Insights on biogeographic and latitudinal distribution. (19th January 2020) - Ribeiro, Karine F.; Ferrero, Ana P.; Duarte, Leandro; Turchetto‐Zolet, Andreia C.; Crossetti, Luciane O.
Abstract: Aim: Free‐living bacteria have long been assumed to have little biogeographic signature because of their high potential for passive dispersal. Raphidiopsis raciborskii and Microcystis aeruginosa are free‐living cosmopolitan cyanobacteria with a probable tropical origin, that frequently form toxic blooms and are considered invasive species in middle latitudes. Despite these similarities, their phylogeographic patterns have seldom been directly compared. Our aim was to reconstruct the phylogeographic histories of R. raciborskii and M. aeruginosa, in order to explore whether their current distributions could be attributed to the same biogeographic events. Location: Global. Taxa: Raphidiopsis raciborskii (Nostocales) and Microcystis aeruginosa (Chroococcales). Methods: The phylogeography of these species was studied based on global genetic diversity patterns from a dataset of worldwide 16S rRNA gene sequences. Genetic diversity indices were measured globally and by latitude. Analyses based on distance matrices were performed to evaluate the correlation between genetic divergence, geographic distance and climatic conditions. Demographic history was investigated through neutrality tests and Bayesian Skyline Plot analysis. Results: For both species, the genetic diversity is highest in tropical latitudes, and the data provided evidence of recent population expansions (in the last 2, 500 years). R. raciborskii showed much lower genetic diversity than M. aeruginosa . A significant phylogeographic structure was found for R. raciborskii but not for M. aeruginosa . Climatic conditions had a significant influence on the genetic structure of both species, but this influence was stronger and varied according to latitude only for R. raciborskii . Main Conclusions: Supporting the hypothesis of a tropical origin and recent dispersal to temperate habitats, both species had higher genetic diversity in tropical latitudes and showed evidence of recent population expansions. R. raciborskii populations showed a significant decline in genetic similarity with increasing geographic distance, indicating an interaction between drift and some dispersal limitation on its phylogeography. In contrast, M. aeruginosa seemed to have a high frequency of intercontinental dispersal. Finally, the particularities of each species, such as the ability to form akinetes in R. raciborskii and high genome plasticity and niche specialization in M. aeruginosa, may be associated with the lower genetic diversity of R. raciborskii when compared to M. aeruginosa .